Staphylococcal and Streptococcal Superantigens Trigger B7/CD28 Costimulatory Receptor Engagement to Hyperinduce Inflammatory Cytokines - Popugailo, Andrey; Rotfogel, Ziv; Supper, Emmanuelle; Hillman, Dalia; Kaempfer, Raymond (Frontiers in Immunology, 2019)
Staphylococcal and streptococcal superantigens are virulence factors that cause toxic shock by hyperinducing inflammatory cytokines. Effective T-cell activation requires interaction between the principal costimulatory receptor CD28 and its two coligands, B7-1 (CD80) and B7-2 (CD86). To elicit an inflammatory cytokine storm, bacterial superantigens must bind directly into the homodimer interfaces of CD28 and B7-2. Recent evidence revealed that by engaging CD28 and B7-2 directly at their dimer interface, staphylococcal enterotoxin B (SEB) potently enhances intercellular synapse formation mediated by B7-2 and CD28, resulting in T-cell hyperactivation. Here, we addressed the question, whether diverse bacterial superantigens share the property of triggering B7-2/CD28 receptor engagement and if so, whether they are capable of enhancing also the interaction between B7-1 and CD28, which occurs with an order-of-magnitude higher affinity. To this end, we compared the ability of distinct staphylococcal and streptococcal superantigens to enhance intercellular B7-2/CD28 engagement. Each of these diverse superantigens promoted B7-2/CD28 engagement to a comparable extent. Moreover, they were capable of triggering the intercellular B7-1/CD28 interaction, analyzed by flow cytometry of co-cultured cell populations transfected separately to express human CD28 or B7-1. Streptococcal mitogenic exotoxin Z (SMEZ), the most potent superantigen known, was as sensitive as SEB, SEA and toxic shock syndrome toxin-1 (TSST-1) to inhibition of inflammatory cytokine induction by CD28 and B7-2 dimer interface mimetic peptides. Thus, superantigens act not only by mediating unconventional interaction between MHC-II molecule and T-cell receptor but especially, by strongly promoting engagement of CD28 by its B7-2 and B7-1 coligands, a critical immune checkpoint, forcing the principal costimulatory axis to signal excessively. Our results show that the diverse superantigens use a common mechanism to subvert the inflammatory response, strongly enhancing B7-1/CD28 and B7-2/CD28 costimulatory receptor engagement.